Light-controlled tunable terahertz filters based on photoresponsive liquid crystals. (18th December 2018) - Yan, Dexian; Li, Jiusheng; Jin, Lufan
Abstract: We theoretically propose and investigate a light-controllable narrow-band terahertz (THz) filter and a dual-wavelength filter employing a square lattice photonic crystal with point and line defects. The point defects filled the photoresponsive liquid crystal. The change of the refractive index of the liquid crystal mixture material caused by the linearly polarized ultraviolet (UV) light and visible light results in a shift of the resonant wavelength of the cavity in the filter. We calculate transmittance spectra for the proposed THz wave filters, which have a full width at half maximum of 10 GHz and a transmittance of 95% at the resonant frequencies. By changing the polarized directions of UV and visible light, the performance characteristics of the filters can be adjusted.